2022
DOI: 10.1136/ard-2022-223035
|View full text |Cite
|
Sign up to set email alerts
|

Global epidemiology of systemic lupus erythematosus: a comprehensive systematic analysis and modelling study

Abstract: ObjectivesTo quantify global, regional and country-specific estimates of epidemiology of systemic lupus erythematosus (SLE).MethodsFour databases were systematically searched, and a Bayesian hierarchical linear mixed model was constructed to estimate the global, regional, and country-specific incidence and prevalence of SLE.Results112 studies met the inclusion criteria. The global SLE incidence and newly diagnosed population were estimated to be 5.14 (1.4 to 15.13) per 100 000 person-years and 0.40 million peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(122 citation statements)
references
References 29 publications
(53 reference statements)
2
80
1
1
Order By: Relevance
“…First, Calado et al (2009)observed that in bone marrow CD34 + cells, androgen and estradiol could stimulate telomerase activity, which plays an important role in maintaining the length of telomeres; moreover, androgen also mediated telomerase activity in both normal peripheral blood lymphocytes. Their findings may indicate a significant difference between males and females in the incidence of SLE (Tian et al, 2022) and AS (Tarannum et al, 2022;Zhang et al, 2022). The antigen presentation process stimulates telomerase in normal B cells and T cells, leading to increased telomerase activity (Igarashi and Sakaguchi, 1997;Hathcock et al, 2005).…”
Section: Potential Mechanismsmentioning
confidence: 98%
“…First, Calado et al (2009)observed that in bone marrow CD34 + cells, androgen and estradiol could stimulate telomerase activity, which plays an important role in maintaining the length of telomeres; moreover, androgen also mediated telomerase activity in both normal peripheral blood lymphocytes. Their findings may indicate a significant difference between males and females in the incidence of SLE (Tian et al, 2022) and AS (Tarannum et al, 2022;Zhang et al, 2022). The antigen presentation process stimulates telomerase in normal B cells and T cells, leading to increased telomerase activity (Igarashi and Sakaguchi, 1997;Hathcock et al, 2005).…”
Section: Potential Mechanismsmentioning
confidence: 98%
“…In our case, the patient had class V membranous lupus nephritis. He was started on methylprednisolone injections for three days, then switched to oral prednisolone for the flare and started on mycophenolate mofetil [15][16][17][18]. Because our patient did not improve on the initial doses, the doses were increased until he showed symptomatic improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the overactivation of the immune system and the involvement of various organs. The global systemic lupus erythematous (SLE) incidence and newly diagnosed population were estimated to be 5.14 (1.4 to 15.13) per 100,000 person-years and 0.40 million people annually, respectively (1). Mortality from SLE is two to three times higher than that of the general population (2) and was the underlying cause of over 50,000 deaths from 1968 to 2012 (3).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that dysbiosis in the vagina is evident in patients with primary Sjögren's syndrome (PSS) (20), a systemic inflammatory autoimmune disease that shares epidemiological, clinical, pathogenic, and etiological features with SLE (21, 22). In addition, women are more frequently affected by SLE than men (1). Therefore, we questioned whether there might be a distinct vaginal microbiome signature of SLE in women.…”
Section: Introductionmentioning
confidence: 99%